2015
DOI: 10.1039/c4tc02008a
|View full text |Cite
|
Sign up to set email alerts
|

Cyano substituted benzothiadiazole: a novel acceptor inducing n-type behaviour in conjugated polymers

Abstract: The displacement of fluoride by cyanide offers a simple route to strongly electron accepting cyano substituted benzothiadiazole monomers. Copolymerisation with electron rich donors leads to low band gap polymers which exhibit electron transporting behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 53 publications
10
101
0
2
Order By: Relevance
“…Scheme 1. Synthetic procedures for a) monomer bis-Br(DTCNBT) b) monomer bis-Br(DTDCNBT) 34 and c) polymers P(Ge-DTBT) 26 , P(Ge-DTCNBT), P(Ge-DTDCNBT). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Table 1: Molecular weights and optical properties of P(Ge-DTBT), P(Ge-DTCNBT) and P(Ge-DTDCNBT) a Molecular weights measured using gel permeation chromatography (against polystyrene standards) in chlorobenzene at 80°C.…”
Section: Synthesis Of Monomers and Polymersmentioning
confidence: 99%
“…Scheme 1. Synthetic procedures for a) monomer bis-Br(DTCNBT) b) monomer bis-Br(DTDCNBT) 34 and c) polymers P(Ge-DTBT) 26 , P(Ge-DTCNBT), P(Ge-DTDCNBT). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Table 1: Molecular weights and optical properties of P(Ge-DTBT), P(Ge-DTCNBT) and P(Ge-DTDCNBT) a Molecular weights measured using gel permeation chromatography (against polystyrene standards) in chlorobenzene at 80°C.…”
Section: Synthesis Of Monomers and Polymersmentioning
confidence: 99%
“…63,69,[85][86][87][88][89][90] The previously mentioned polymer 21 originally synthesized by Heeney and coworkers was also examined as a component of TFTs with a promising mobility of 0.11 cm 2 V -1 s -1 noted. 87 Similarly, the previously described dithienogermole and germafluorene copolymers 54-60 ( Fig.…”
Section: Transistors and Semi-conducting Materialsmentioning
confidence: 99%
“…[13][14][15][16] For example, we have previously shown that replacing dithienyl benzothiadiazole (DTBT) with dithienylthiadiazolopyridine (DTPyT) could lead to a lowered LUMO level (by ~ 0.3 eV) and a narrowed band gap (by ~ 0.2 eV) when each was copolymerized with BnDT. 13 Inspired by this successful precedent and others, [14][15][16] we envisioned a general modification strategy for the parent benzotriazole (TAZ) (Chart 1), aiming to enhance the electron withdrawing nature of the moiety 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 5 m-TAZ while preserving its other beneficial structural features. However, building such a library of triazole acceptors would be very challenging if one chose to painstakingly synthesize each proposed structural modification of m-TAZ from individual starting materials, though we and others have taken such individualized syntheses for other structurally related acceptors (Scheme S1).…”
Section: Chart 1 General Structure Of Triazole Based Acceptorsmentioning
confidence: 99%